The Role of Transformational Leadership and Self-Efficacy on Readiness to Change Through Work Engagement - Meria, Lista; Saukani; Prastyani, Desy; Dudhat, Amitkumar (Aptisi Transactions On Technopreneurship (ATT), 2022)
Readiness to change is a basic thing that teachers must have to be able to adapt to technology and scientific developments. This study aims to determine the effect of self-efficacy and transformational leadership on job engagement. Then to determine the effect of self-efficacy and transformational leadership on readiness to change. This research is descriptive and quantitative research conducted on 124 junior high school teachers in Pringsewu Lampung using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results showed that self-efficacy and transformational leadership had a positive effect on work engagement. Transformational leadership also has a positive effect on readiness to change, but self-efficacy does not directly affect readiness to change. Furthermore, job engagement mediates the effect of self-efficacy and transformational leadership on readiness to change. This research has implications for being applied to teachers during the process of being more open to accepting change